Iranian Smell Diagnostic Test in Covid-19 Disease; Report of Covid-19 Center of North of Iran - Shayan Alijanpour; Payam Saadat; Mehran Shokri; Sepanta Saadat; Azam Khodami (Babol University of Medical Sciences, 2022)
Background: SARS-CoV-2 is a pandemic coronavirus that causes the COVID-19 syndrome. In the pandemic of COVID-19 many patients were affected to new onset olfactory dysfunction. Since there is a dearth of research studies regarding the standard smell test, the present study was conducted to fill this gap. Methods: The present retrospective cohort study was conducted on 250 clients with or without diagnosis of Covid-19 disease who referred to Covid-19 centers of North of Iran. Two groups were matched for age and sex. Data were collected by examination, demographic and clinical information questionnaire and Iranian smell diagnostic test. The binary logistic regression to estimate the odds ratio value in SPSS version 23.0 was used. Results: One-hundred cases (42.2%) had hyposmia and 20 cases (8.4%) were found to have anosmia. Type of covid-19 sign and symptom were statistically significant with olfactory dysfunction (41 cases, 31.8%), fever (28 cases, 21.7%), weakness and dyspnea (15 cases, 11.6%), (p=0.0001). The urban residency equal OR=6.42 (3.04-13.53) to rural residency for olfactory dysfunction (p=0.0001). Covid-19 patients' OR=61.25 (27.36-137.11) chance to be affected by the olfactory dysfunction in compare to control group (p=0.0001). Also, with increasing age, chance of olfactory dysfunction changed from OR=0.61(1.16-0.13) to OR=1.89 (0.82-4.33). Furthermore, female chance OR=1.21 (0.72-2.03) and employee patients was OR=2.29 (1.30-4.04) to olfactory dysfunction. Conclusion: Alf of the patients were affected by olfactory dysfunction. Furthermore, Covid-19 patients, urban residency, lower age, female and employee were the prognostic factors for olfactory dysfunction. The standard olfactory tests such as IR-SIT is suggested for screening and detecting the clients probably affected by covid-19 especially in younger ages.